Picturing Students' Habitus: The Advantages and Limitations of Photo-Elicitation Interviewing in a Qualitative Study in the City of Buenos Aires - Meo, Analía Inés (2010)
In this paper the author examines some advantages and limitations of the use of photoelicitation interviews in a study on class habitus, identities, and schooling in two secondary schools in the city of Buenos Aires (Argentina). First, she describes her research questions, methodological strategy, and application of photo elicitation technique, which refers to the use of a single or set of photographs as stimulus during a research interview. Second, she assesses the benefits and problems of its application by making comparisons between both different photo-interviews and interviews with and without photographs. This exercise allows the author to identify the benefits of photo-elicitation, such as the opening up of unforeseen dimensions for analysis and the facilitation of a rapport with respondents; and some disadvantages, for example, the possibility of the “closing communication” effect between researcher and participant.